2016
DOI: 10.1016/j.tcb.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Microglia: Architects of the Developing Nervous System

Abstract: Microglia are resident macrophages of the central nervous system (CNS), representing 5–10% of total CNS cells. Recent findings reveal that microglia enter the embryonic brain, take up residence before the differentiation of other CNS cell types, and become critical regulators of CNS development. Here, we discuss exciting new work implicating microglia in a range of developmental processes including regulation of cell number and spatial patterning of CNS cells, myelination, and formation and refinement of neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
210
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(225 citation statements)
references
References 111 publications
2
210
0
Order By: Relevance
“…This has been noted in other developing CNS structures, such as the cerebral cortex [39]. Why microglia in many regions of the developing brain display the activated phenotype has not yet been determined, but may be related to the developmental functions attributed to microglial cells, including regulation of cell number and spatial patterning of CNS cells, myelination, and formation and refinement of neuronal circuits [48]. …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This has been noted in other developing CNS structures, such as the cerebral cortex [39]. Why microglia in many regions of the developing brain display the activated phenotype has not yet been determined, but may be related to the developmental functions attributed to microglial cells, including regulation of cell number and spatial patterning of CNS cells, myelination, and formation and refinement of neuronal circuits [48]. …”
Section: Discussionmentioning
confidence: 96%
“…We show for the first time that microglia begin to colonize the rat pineal neuroepithelium at the earliest stage of gland formation before pinealocyte differentiation has commenced (Fig 5A 1 –5A 5 ). This timing of microglial colonization is a common feature in the developing brain [48]. Microglia appear to populate the pineal primordium from the meninges and also from the choroid plexus of the third ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia are critical to the development of the embryonic and postnatal brain (Frost and Schafer 2016), yet data connecting early microglia function to behavioral maturation is currently lacking. One such study, published during the preparation of this manuscript, used a similar approach to address this issue (Nelson and Lenz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that microglia are most critical for establishing brain architecture and circuitry necessary for normal behavior (Frost and Schafer, 2016), and little research has investigated the influence of microglia on the organization of brain and behavior during early periods of development.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, microglia are involved in synaptic pruning and may release neurotrophic factors, including insulin-like growth factor 1 and brain-derived neurotrophic factor, demonstrating that these cells are architects in the developing brain [16][17][18][19][20]. Based on studies in mice, synaptic pruning might be achieved via a complement-dependent mechanism because disruption of complement receptor 3 on microglia led to deficits in synaptic engulfment [21,22].…”
Section: Trem2: Presenting Microglia Front and Center In Admentioning
confidence: 99%